Acute estradiol protects CA1 neurons from ischemia-induced apoptotic cell death via the PI3K/Akt pathway - Jover-Mengual, Teresa (2010)
Global ischemia arising during cardiac arrest or cardiac surgery causes highly selective, delayed death of hippocampal CA1 neurons. Exogenous estradiol ameliorates global ischemia-induced neuronal death and cognitive impairment in male and female rodents. However, the molecular mechanisms by which a single acute injection of estradiol administered after the ischemic event intervenes in global ischemia-induced apoptotic cell death are unclear. Here we show that acute estradiol acts via the phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) signaling cascade to protect CA1 neurons in ovariectomized female rats. We demonstrate that global ischemia promotes early activation of glycogen synthase kinase-3β (GSK3β) and forkhead transcription factor of the O class (FOXO)3A, known Akt targets that are related to cell survival, and activation of caspase-3. Estradiol prevents ischemia-induced dephosphorylation and activation of GSK3β and FOXO3A, and the caspase death cascade. These findings support a model whereby estradiol acts by activation of PI3K/Akt signaling to promote neuronal survival in the face of global ischemia.